Question 4:
If a2 – 2a – 1 = 0, then = __________.
Answer 4:
Hence, if a2 – 2a – 1 = 0, then = 6.
Question 5:
If a2 + b2 + c2 = 24 and ab + bc + ca = – 4, then a + b + c = ________.
Answer 5:
Hence, if a2 + b2 + c2 = 24 and ab + bc + ca = – 4, then a + b + c = ±4.
Question 6:
If x + y + z = 0, then (x + y)3 + (y + z)3 + (z + x)3 = ________.
Answer 6:
Hence, if x + y + z = 0, then (x + y)3 + (y + z)3 + (z + x)3 = −3xyz.
Question 7:
If x + y + z = 5 and xy + yz + zx = 7, then x3 + y3 + z3 – 3xyz = _________.
Answer 7:
Hence, if x + y + z = 5 and xy + yz + zx = 7, then x3 + y3 + z3 – 3xyz = 20.
Question 8:
If (a + b + c) {(a – b)2 + (b – c)2 + (c – a)2} = k(a3 + b3 + c3 – 3abc), then k = ________.
Answer 8:
Hence, if (a + b + c) {(a – b)2 + (b – c)2 + (c – a)2} = k(a3 + b3 + c3 – 3abc), then k = 2.
Question 9:
If
Answer 9:
Hence, if
Question 10:
If
Answer 10:
Hence, if
Question 11:
If
Answer 11:
Hence, if
Question 12:
If
Answer 12:
Hence, if
No comments:
Post a Comment